Moses : in the footsteps of the reluctant prophet - Hamilton, Adam, 1964- (Nashville : Abingdon Press, 2017)
Turn your reluctance into boldness by walking in the footsteps of Moses.
The birth of Moses -- Two moments that defined the man -- The Exodus -- The Ten commandments -- Lessons from the wilderness -- Don't forget ... pass it on.
Includes bibliographical references.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Master record variable field(s) change: 630
Keywords: Moses -- (Biblical leader); RELIGION / Biblical Studies / Old Testament; Electronic books; Electronic books